2017
DOI: 10.1097/spc.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment following hormone therapy: current opinion of research in breast and prostate cancer patients

Abstract: Purpose of review Hormone therapy is a common cancer treatment that may be associated with numerous side and late effects, and in recent years, has been linked to changes in cognition. Here, we present the most important recent findings from empirical studies and reviews that have focused on the effects of hormone therapy on cognitive functioning in breast and prostate cancer populations, underline some general shortcomings, and propose directions for future research. Recent Findings Recent research indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…With advances in treatments (e.g., chemotherapy, immunotherapies), BC survival rates have increased [ 2 , 3 ]; however, systemic chemotherapy can cause adverse reactions [ 3 ]. Although severe neurotoxic events are rare, risks of cognitive decline have varied in their estimates from 15~60% to the extent of interfering with the quality of everyday life [ 3 , 4 , 5 , 6 , 7 ]. Specifically, impairments in attention, concentration, learning, processing speed, and executive functioning have been reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in treatments (e.g., chemotherapy, immunotherapies), BC survival rates have increased [ 2 , 3 ]; however, systemic chemotherapy can cause adverse reactions [ 3 ]. Although severe neurotoxic events are rare, risks of cognitive decline have varied in their estimates from 15~60% to the extent of interfering with the quality of everyday life [ 3 , 4 , 5 , 6 , 7 ]. Specifically, impairments in attention, concentration, learning, processing speed, and executive functioning have been reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the changes in cognitive function associated with AI therapy because few studies have focused on cognitive function with these agents. In addition, methodologic issues reduce the ability to compare results across studies (Wu & Amidi, 2017). Samples in some studies were heterogeneous, combining premenopausal with postmenopausal women (Ganz et al, 2014; Hermelink et al, 2008; Jenkins et al, 2006; Palmer et al, 2008) and women who received AIs with women who received SERMs (Collins, Mackenzie, Stewart, Bielajew, & Verma, 2009; Ganz et al, 2014; Mar Fan et al, 2007; Root, Andreotti, Tsu, Ellmore, & Ahles, 2016; Schilder et al, 2009).…”
mentioning
confidence: 99%
“…On the other, it has been suggested that chemotherapy and hormone therapy produce cognitive deficits (Dietrich & Kaiser, 2016; Wu & Amidi, 2017). One of the cognitive domains most referenced in this field is that of the executive functions (Vitali et al, 2017; Yao, Bernstein & Rich, 2017).…”
Section: Discussionmentioning
confidence: 99%